2020
DOI: 10.1016/j.fertnstert.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 in human semen—a cohort study

Abstract: Objective: To investigate the presence of viral RNA in human semen of patients with severe acute-respiratory syndrome coronavirus 2 (SARS-CoV-2) and to evaluate its presence and relevance in semen parameters. Design: Pilot cohort study. Setting: University hospital. Patient(s): Thirty-four men were distributed as: 1) patients in convalescence (patients with confirmed SARS-CoV-2 infection in pharyngeal swab according to reverse-transcription polymerase chain reaction [RT-PCR] or antibodies); 2) negative control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
474
7
29

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(529 citation statements)
references
References 18 publications
19
474
7
29
Order By: Relevance
“…They have shown the absence of SARS-COV-2 in semen samples in 12 recovered patients and in the testes of one deceased patient during acute infection [17]. Similarly, Holtmann et al [18] reported absence of SARS-CoV-2 in the semen of 34 patients. Only 2 of them were in the acute stage.…”
Section: Discussionmentioning
confidence: 98%
“…They have shown the absence of SARS-COV-2 in semen samples in 12 recovered patients and in the testes of one deceased patient during acute infection [17]. Similarly, Holtmann et al [18] reported absence of SARS-CoV-2 in the semen of 34 patients. Only 2 of them were in the acute stage.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Angiotensin-converting enzyme 2 (ACE2), the receptor used by the virus to enter human cells, has been identified in human testis as it is highly expressed in Leydig, Sertoli, and seminiferous tubules cells, and new findings suggest a possible expression of ACE2 even in spermatocytes. At the time of this article, few studies looking for the presence of SARS-CoV-2 in human semen are available but have come to discordant conclusions [1][2][3][4][5]. In particular, while the detection of SARS-CoV-2 RNA in semen during the acute phase of severe symptomatic infections has already been demonstrated, weaker evidence has been shown of virus shedding through semen in the recovery phase or convalescence of COVID-19 and in patients with mild symptoms or in asymptomatic cases.…”
Section: To the Editormentioning
confidence: 99%
“…Interestingly, in-situ hybridization of testicular tissue specimens does not recognize viral genomic materials [8]. Moreover, studies could not yet find viral trace in the seminal plasma [9,10]. This indicates that inflammatory and immunologic reactions take pivotal role in the viral-mediated testicular damage.…”
mentioning
confidence: 99%